BASES OF DESIGN AND CALCULATION OF REINFORCED CONCRETE STRUCTURES - Hud, Mykhailo; Meshcheryakova, Olga; Kachor, Andrii; Hud, Volodymyr (SWorld-Ger Conference proceedings, 2023)
The article explores the essential principles and methodologies involved in the design and calculation of reinforced concrete structures. Reinforced concrete has become a fundamental material in contemporary construction due to its versatility, durability